INFORMATION SYSTEM FOR SALES OF HIJABS AT ANAK KULIAHAN SHOPS USING THE RAPID APPLICATION DEVELOPMENT METHOD - Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to design and implement a sales information system for hijabs at Anak Kuliahan Shop using the Rapid Application Development (RAD) method. RAD was chosen for its capabilities in rapid software development, allowing continuous iteration and modification based on user feedback. This study adopted a qualitative and quantitative approach, starting with needs analysis through interviews with shop owners and customer surveys to identify desired features and functions in the system. Next, a system prototype is developed and tested over several cycles, with adjustments made based on evaluations from early users. The research results show that the implementation of a RAD based sales information system at the Anak Kuliahan Store has succeeded in increasing operational efficiency, speeding up the sales transaction process, and providing accurate sales analytics for strategic decision making. This system also increases customer satisfaction through a more convenient shopping experience and personalized service. In addition, the system supports more effective inventory management, enabling Toko Anak Kuliahan to respond quickly to market demand and hijab fashion trends. This research concludes that the RAD method is an effective approach in developing sales information systems for small retail businesses such as Toko Anak Kuliahan. The use of RAD facilitates the development of systems that are responsive to business needs and customer preferences.